Bayesian prediction and adaptive sampling algorithms for mobile sensor networks : online environmental field reconstruction in space and time /: online environmental field reconstruction in space and time. ([2016]) - Xu, Yunfei; Choi, Jongeun; Dass, Sarat Chandra; Maiti, Tapabrata
No abstract available